THE IMPLEMENTATION OF THE INFORMATION TECHNOLOGY SYSTEM TO IMPROVE HEALTH SERVICE - Hidayah, Nur; Aini, Qurratul; Amin, Muh (The journal of contemporary issues in business and government, 2021)
The improvement of information technology in health services can improve health services in hospitals. In the long term, information technology will increase hospitals’ efficiency, effectiveness, and productivity in achieving the hospital vision. This study aimsto obtain the most appropriate information technology system in the private hospital in Central Java, Indonesia. This study involved a case study method by conducting Focus Group Discussion (FGD), documentation study, and interview in stages to find out the right strategy as a part of the strategic plan for the years 2021-2025. FGD participants were the work unit managers who are members of the Hospital Strategic Plan Team. The result pointed out that the hospital hadimplemented a technology information system to provide services to patients from registration, electronic medical records specifically for pediatric and neurological polyclinics to the billing system. Information and communication technology will be implemented until the next five years consisting of an online human resource (HR) management information system, an online financial management information system, an onlineoperational management system, and Electronic Medical Records for all policlinics.